1986
DOI: 10.1007/bf00283934
|View full text |Cite
|
Sign up to set email alerts
|

Synapsis and synaptic adjustment in an infertile human male heterozygous for a pericentric inversion in chromosome 1

Abstract: Synapsis and "synaptic adjustment" were analyzed, using electron microscopy in silver stained surface microspreads of inversion-bearing spermatocytes, in an infertile human male with an inherited pericentric inversion in chromosome 1. Possible reasons for his infertility are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0
2

Year Published

1987
1987
2004
2004

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
1
17
0
2
Order By: Relevance
“…However, none of these studies have studied reciprocal translocations involving chromosome 1, and the studies of three different inversions involving chromosome 1 have failed to confirm any association to the XY-body. 17,29,30 An association with the XY-body is especially frequent when acrocentric chromosomes are involved in the rearrangements. 28 In the present study, we observed a significant excess of infertile males with a breakpoint on an acrocentric p-arm.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of these studies have studied reciprocal translocations involving chromosome 1, and the studies of three different inversions involving chromosome 1 have failed to confirm any association to the XY-body. 17,29,30 An association with the XY-body is especially frequent when acrocentric chromosomes are involved in the rearrangements. 28 In the present study, we observed a significant excess of infertile males with a breakpoint on an acrocentric p-arm.…”
Section: Discussionmentioning
confidence: 99%
“…1982;Moses and Poorman, 1984;Tease and Fisher, 1986), pericentric inversion (Ashley et al, 1981;Davisson et al. 1981;Gabriel-Robez et al, 1986b;Guichaoua et al, 1986), centric fusion (Moses et al, 1979;Bogdanov et al. 1986), tandem duplication (Moses andPoorman.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of these cell anomalies declined from late zygotene to late pachytene. This could be because synaptic adjustment reduces pairing failures, as has been proposed for several mammalian species (Ashley et al, 1981;Moses and Poorman, 1981;Gabriel-Robez et al, 1986;Dollin et al, 1991).…”
Section: Resultsmentioning
confidence: 86%